Android: S-Based Technique in Mobile Malware Detection - Rahiwan Nazar, Romli (2017)
Mobile malware is a serious threat in mobile security. Malware detector is the primary tool and first defense to protect mobile device against mobile malware. The impact of malware is negative. It causes files to be corrupted and secret information being compromised. Nowadays malware writers try to avoid detection from malware detectors using several techniques such as polymorphism and metamorphism. In order to overcome malware, concern in mobile, we propose a new framework for malware detection which is signature based technique using pattern matching. This framework uses signature number and Secure Hash Algorithm (SHA) as signature in the detection process. Both features will be examined by sequence in order to detect leakage of information. As a result, a file that considered as suspicious or malware will be sent to cloud for analyzing and classification.